Analisis Penerapan Manajemen Resiko dalam Pembiayaan Usaha Mikro pada Pt Permodalan Nasional Madani (Persero) Unit Aksara - Muhammad Rozzaq Pane; Nicholas Marpaung (Regress: Journal of Economics & Management, 2022)
This article aims to analyze how the application of risk management in micro business financing at PT Permodalan Nasional Madani Aksara Unit so that it can be seen how far the risk management that is already owned by the company to overcome the existing risks. The results of this study indicate that the risk of late payment of financing installments to not being able to pay off their obligations is the main problem faced by the company, but the company has prepared risk management in dealing with these risks, there are pre-risk and post-risk management stages owned by the company in order to facing the risks that occur or will occur with the aim of minimizing the losses experienced by the company has been implemented properly in accordance with the standard financing procedures owned by the company, starting from identifying each risk to controlling so that any risks that occur can be overcome by the company.